Dampak Covid-19 Terhadap Kegiatan Pembelajaran Online Di Sd Negeri 157013 Sibabangun 5 Tapanuli Tengah - Nurhanifa Tamba (Program Studi PGSD Kampus UPI di Serang, 2020)
COVID-19 is an outbreak of disease originating from China which spread rapidly throughout the world. COVID-19 spread in Indonesia in early March 2020. This study aims to identify online learning activities at the homes of students as an effort to support government programs namely study from home during the covid 19 pandemic. The spread of this virus caused losses to several countries, especially in the field of economy. In the field of education, it also changed the learning model drastically; all learning activities are carried out online starting from elementary school level to university level. This research is a qualitative descriptive study describing online learning activities at a elementary school 157013 Sibabangun 5 after the stipulation of all learning activities carried out from home in online mode. Interview was used to collect the data from 2 students, 2 Teachers and 1 Student parents. Based on the interview results, online learning activities at this university have been effective by utilizing the Zoom, Google Classroom, Whatsapp applications. Constraint in implementing online learning mostly is internet connection problems that less supportive.